Benchmarking in QoS and Energy Consumption SAW and TOPSIS Algoritm in Low Cost Microcontroller for Wireless Sensor Network Routing Application - Hakim, Galang Persada Nurani; Septiyana, Diah; Dani, Akhmad Wahyu; Sirait, Fadli (Electrical Engineering, Universitas Mercu Buana, 2024)
The Wireless Sensor Network technologies have provides us with cheap and unique solution to deal with telecommunication infrastructure problem that don’t exist in extreme and isolated area. To guarantee the quality of service of Wireless Sensor Network wireless data transmission, a lot of researchers propose to employ a routing algorithm, such as SAW and fuzzy topsis from MCDM algorithm. A lot of routing algorithm in Wireless Sensor Network was based on these algorithms. In this paper we propose to do simulation and real time energy measurement in order to determine the best MCDM algorithm to be use in Wireless Sensor Network routing. In QoS 3x4 node simulation Both algorithm has provide low delay 31 millisecond and low packet loss 16 bit. This good performance in QoS however has disadvantage which has higher hop quantity. In term of energy consumption SAW has less energy consumption (better) compare with fuzzy topsis for each microcontroller development platforms that we have test. Although it was small but we have difference in energy consumption between SAW and fuzzy topsis, for ESP32 it has difference 39 microJoule, for ESP8266 it has difference 129 microJoule and for ATMEGA328P it has difference 2 microJoule.